High-performance polyether-ether-ketone plate and preparation method thereof
By adding specific nanomaterials and process to polyether ether ketone materials, high-performance polyether ether ketone plates are prepared, which solves the problem of poor application of materials in semiconductor manufacturing, and has achieved significant improvements in the mechanical, electrical conductivity, thermal conductivity and anti-static properties of the materials, meeting the application needs in high temperature and corrosion environments.
Patent Information
- Application Number
- CN202411991329.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-02-28
AI Technical Summary
Existing polyether ether ketone materials are poorly used in semiconductor manufacturing, especially in extreme chemical environments, which cannot meet the requirements of high purity and corrosion resistance. At the same time, their conductivity and anti-static ability are insufficient, which may lead to electrostatic discharge and production errors.
Polyether ether ketone is used as the matrix, carbon nanotubes, graphene nanosheets, conductive tin oxide micropowder, polytetrafluoroethylene micropowder and silane coupling agent are added, and high-performance polyether ether ketone plates are prepared through melt mixing, extrusion molding and hot pressing molding processes, and magnetic powder is added during the coating process and an external magnetic field is applied to optimize the arrangement of the nanomaterials.
It significantly improves the mechanical properties, conductivity, thermal conductivity and anti-static properties of the material, and can maintain excellent durability and reliability in high temperature, corrosion and fatigue resistance environments, meeting the high purity and corrosion resistance requirements of semiconductor manufacturing.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a high-performance polyetheretherketone board and a preparation method thereof, belonging to the technical field of semiconductor manufacturing. Background Art
[0002] Semiconductor silicon wafers are the core material in semiconductor manufacturing. Their production and processing involve precision polishing, grinding, etching, cleaning and other processes. This process requires the use of some high-purity chemicals, such as hydrofluoric acid (HF), hydrogen chloride (HCI), sodium hydroxide (NaOH) and other strong acids and alkalis, which puts forward extremely high requirements on corrosion resistance and chemical resistance for processing accessories and pipeline transportation and storage materials. Fluoropolymers are the only materials that can accommodate and transport high-purity chemicals used in the manufacturing process, achieving the extremely high stability and purity required for semiconductor manufacturing.
[0003] The existing technology directly uses fluorine materials for injection molding, extrusion, molding and other forms, and mostly uses fluorine resin profiles to process various parts required in the semiconductor production process. The amount of fluorine resin used in the existing technology is still very large.
[0004] Polyetheretherketone material is known for its excellent mechanical properties, chemical stability and thermal stability. It is also widely used in the semiconductor industry. However, in some special chemical environments, the role of fluoroplastics is irreplaceable, especially the tolerance to extreme chemical environments and high purity maintenance require high temperature resistance, chemical corrosion resistance and other characteristics. Therefore, we selected PEEK material as the base material and sprayed fluororesin on it. The produced profiles can not only meet the characteristic requirements in the semiconductor processing link, but also effectively reduce and reduce the use of fluoroplastics to meet the demands of environmental protection. However, pure PEEK material has poor electrical conductivity and poor antistatic ability, and static electricity accumulation will occur. Electrostatic discharge (ESD) may cause tiny currents, damage sensitive components, and lead to production errors, thus failing to meet the application in semiconductor manufacturing. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a high-performance polyetheretherketone board and a preparation method thereof, which solves the problem of poor applicability of polyetheretherketone materials in semiconductor manufacturing in the prior art.
[0006] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions: A high-performance polyetheretherketone board comprises the following components in parts by weight: 80-90 parts of polyetheretherketone; 1 to 3 parts of carbon nanotubes; 1 to 3 parts of graphene nanosheets; 2-5 parts of conductive tin oxide powder; 3-5 parts of polytetrafluoroethylene powder; Silane coupling agent 0.5 to 1 part.
[0007] By adopting the above technical solution, polyetheretherketone (PEEK) as the matrix of the composite material provides high strength, excellent heat resistance and corrosion resistance, ensuring the overall mechanical properties and thermal stability. The addition of carbon nanotubes (CNT) and graphene nanosheets improves the electrical conductivity, mechanical strength and thermal conductivity of the composite material. Carbon nanotubes have extremely high specific surface area and excellent electrical conductivity. Their good interface interaction with polyetheretherketone and other nanomaterials improves the strength and rigidity of the material. The synergistic effect between graphene nanosheets and carbon nanotubes forms a conductive network, thereby enhancing the overall electrical conductivity and thermal management performance. Conductive tin oxide powder (SnO 2 ) as a conductive filler can further strengthen the conductive network of the composite material, and work synergistically with carbon nanotubes and graphene to provide a more efficient conductive path. Polytetrafluoroethylene powder (PTFE) has excellent chemical resistance and low friction coefficient, which can improve the friction and wear resistance of the composite material without affecting its conductivity. Silane coupling agent enhances the interfacial bonding between polyetheretherketone and filler, improves dispersibility and mechanical properties, and improves the long-term stability of the material.
[0008] Strong acids, strong alkalis and other chemicals often generate a certain amount of frictional heat during transportation, especially when flowing in pipelines. If the frictional heat cannot be dissipated in time, it may cause local overheating, which in turn affects the stability and life of the material. Combining the low friction characteristics and high thermal conductivity of polytetrafluoroethylene (PTFE) and graphene nanosheets into polyetheretherketone (PEEK) can significantly enhance its application advantages in transporting strong acids, strong alkalis and other chemical media. The self-lubricating properties provided by PTFE can reduce friction and wear, while the high thermal conductivity of graphene effectively disperses frictional heat to prevent heat accumulation and overheating.
[0009] Combining polytetrafluoroethylene (PTFE) micropowder with carbon nanotubes (CNT) for polyetheretherketone (PEEK) plates significantly improves its fatigue resistance, wear resistance and durability in the transportation of strong acids and alkalis. The lubricating effect of PTFE effectively reduces the wear of stress concentration areas and delays the expansion of fatigue cracks, while the enhanced mechanical properties of carbon nanotubes improve the strength and rigidity of the material. This composite material can withstand long-term cyclic stress in high pressure, high temperature and corrosive environments.
[0010] The present invention is further configured as follows: the carbon nanotubes and graphene nanosheets are respectively coated with polyaniline or polypyrrole.
[0011] First, carbon nanotubes and graphene nanosheets themselves have very high specific surface areas and unique electronic structures, but when mixed with the polyetheretherketone matrix, due to their low hydrophilicity, they are easy to aggregate and agglomerate, resulting in uneven dispersion in the composite material, which in turn affects the mechanical properties and electrical conductivity of the material. This problem can be effectively overcome by coating carbon nanotubes and graphene nanosheets with polyaniline or polypyrrole. Polyaniline and polypyrrole are conductive polymers with strong dispersing effects. They can form a uniform coating layer on the surface of carbon nanotubes and graphene nanosheets, thereby reducing the mutual attraction between these nanomaterials and improving their dispersibility in the matrix. Well-dispersed nanofillers can form a more uniform conductive network in the polyetheretherketone matrix, greatly improving the electrical conductivity and mechanical strength of the composite material.
[0012] Secondly, the coating of polyaniline and polypyrrole also enhances the interfacial bonding between carbon nanotubes and graphene nanosheets and the polyetheretherketone matrix. Polyaniline and polypyrrole not only have good chemical stability and heat resistance, but also their molecular structure can interact with the molecular chains in the PEEK matrix to form a strong interfacial connection. This strong interfacial bonding helps to improve the mechanical properties of the composite material, such as tensile strength, hardness and rigidity, and avoids interfacial slip and brittle fracture between the nanomaterial and the matrix.
[0013] In addition, the conductive properties of polyaniline and polypyrrole coating materials further enhance the conductivity of the composite material. These conductive polymers not only improve the efficiency of electron transfer between nanomaterials, but also improve the electronic interface contact between nanomaterials and the matrix, effectively improving the overall conductivity of the composite material.
[0014] The present invention is further configured as follows: magnetic powder is mixed into the coating process, and the magnetic powder is ferrite powder, cobalt iron oxide powder or nano iron powder; the average particle size of the magnetic powder is 100 nanometers to 500 nanometers.
[0015] The present invention is further configured such that an external magnetic field is applied to the polyetheretherketone plate during the melt mixing process.
[0016] The present invention is further configured such that the intensity of the external magnetic field is 0.5 to 2 Tesla.
[0017] The present invention further optimizes the electrical conductivity and thermal management performance of the composite material by mixing magnetic powder (such as ferrite powder, cobalt iron oxide powder or nano iron powder) during the coating process. The addition of magnetic powder can regulate the arrangement direction of nanomaterials through the magnetic field, help form a more orderly conductive network, and promote the improvement of electronic conduction efficiency. At the same time, magnetic powder also has a certain effect on the improvement of thermal conductivity, especially in high temperature environments, it can effectively disperse local heat, reduce the risk of heat accumulation, and improve the thermal stability of the material.
[0018] Secondly, the external magnetic field can not only further optimize the arrangement of magnetic powder, but also make the one-dimensional carbon nanotubes and two-dimensional graphene nanosheets more orderly arranged, thus forming a more efficient conductive network in the composite material. By precisely adjusting the magnetic field strength (0.5 to 2 Tesla), the directional arrangement of carbon nanotubes and graphene nanosheets can be controlled, so that the composite material exhibits better performance in terms of conductivity and antistatic properties. Especially in the field of electrostatic protection, this conductive network with a highly ordered structure can effectively disperse and eliminate static charges and improve the antistatic ability of the material.
[0019] The present invention is further configured as follows: the coating step is specifically as follows: Step 1: Prepare Materials: 1) Acid treatment or ultrasonic dispersion of carbon nanotubes and graphene nanosheets to obtain surface pretreated fillers; 2) Prepare a monomer solution of polyaniline (PANI) or polypyrrole (PPy), the concentration of which is 0.2 mol / L, and add an oxidant to start the polymerization reaction. The oxidant is ammonium persulfate (APS), and the amount added is 0.1 to 0.2 times the mass of the monomer; at the same time, select magnetic powder (such as nano iron powder or ferrite powder) and disperse it in the monomer solution of polyaniline (PANI) or polypyrrole (PPy), and the amount of the magnetic powder added is 10 to 15% of the mass of the filler; Wherein, the mass ratio of polyaniline (PANI) or polypyrrole (PPy) monomer solution to carbon nanotubes and graphene nanosheets is 2:1 to 10:1; Step 2: Coating reaction: Add the treated carbon nanotubes and graphene nanosheets to the monomer solution of polyaniline or polypyrrole containing magnetic powder, stir at room temperature for 2 to 4 hours to complete the polymerization coating. For polyaniline coating reaction, the temperature should be controlled at 25 to 30°C and the reaction time is 2 to 4 hours; for polypyrrole coating reaction, the temperature should be controlled at 0 to 5°C and the reaction time is 6 to 8 hours; Step 3: Drying and crushing: The product after the coating reaction is separated by filtration and washed with deionized water until it is neutral; the washed coating material is vacuum dried, the temperature is controlled at 50-60°C, and the drying time is 12 to 24 hours; the dried coated particles are crushed to obtain the desired particle size, and the particle size range is 10-50 microns.
[0020] The coating step of the present invention significantly improves the dispersibility, interfacial bonding force and overall performance of the carbon nanotubes and graphene nanosheets through precise reaction control and material selection. First, the carbon nanotubes and graphene nanosheets are surface pretreated by acid treatment or ultrasonic dispersion to remove impurities and improve their affinity, thereby ensuring good dispersibility of the filler in subsequent reactions. Then, the monomer solution of polyaniline or polypyrrole and magnetic powder (such as nano iron powder or ferrite powder) work together to form a uniform coating layer, improve the dispersibility of the filler and improve its interfacial bonding force with the polyetheretherketone matrix. The addition of magnetic powder helps to optimize the conductive network and thermal conductivity path, and improve the conductivity and thermal stability of the composite material. By precisely controlling the temperature and time of the coating reaction, the uniformity and stability of the coating layer are guaranteed, and adverse reactions or excessive polymerization of the polymer are avoided. Finally, the particle size of the coated particles is controlled within the range of 10 to 50 microns by vacuum drying and pulverization, thereby optimizing the fluidity, processability and uniformity of the composite material. This series of coating processes significantly improves the electrical conductivity, thermal conductivity, antistatic and mechanical properties of the composite material, making the final polyetheretherketone composite material have excellent durability and reliability in harsh environments such as high temperature, corrosion and fatigue resistance.
[0021] The present invention is further configured as follows: during the coating process, the amount of magnetic powder coated on the carbon nanotubes is 1-3% of the total weight of the carbon nanotubes, and the amount of magnetic powder coated on the graphene nanosheets is 3-5% of the total weight of the graphene nanosheets.
[0022] For carbon nanotubes, adding 1-3% magnetic powder helps to further improve the thermal conductivity and antistatic ability of the composite material while maintaining its good electrical conductivity. A lower proportion of magnetic powder can effectively optimize the interface between carbon nanotubes and the polyetheretherketone matrix, ensure the efficient conduction of the conductive network, and avoid excessive filling and bonding of the material caused by excessive addition of magnetic powder, thereby maintaining good mechanical properties. For graphene nanosheets, appropriately increasing the proportion of magnetic powder (3-5%) helps to improve its bonding with the polyetheretherketone matrix, while optimizing the electrical and thermal conductivity of graphene nanosheets. Graphene nanosheets themselves have a large specific surface area and excellent electrical conductivity. An appropriate amount of magnetic powder can promote their directional arrangement through an external magnetic field, further improving the conductive network efficiency and thermal conductivity of the composite material. In addition, the addition of magnetic powder can also improve the dispersibility of graphene nanosheets in the composite material and avoid their aggregation, thereby improving the uniformity and stability of the overall material.
[0023] In summary, controlling the amount of magnetic powder added to carbon nanotubes and graphene nanosheets not only optimizes the conductive network of the composite material, but also enhances the thermal management ability, antistatic properties and mechanical properties of the material, so that the final prepared polyetheretherketone composite material exhibits more excellent comprehensive performance under high temperature, corrosive and anti-fatigue environments.
[0024] A method for preparing a high-performance polyetheretherketone board comprises the following steps: S1: Mix the various raw materials of the high-performance polyetheretherketone board evenly according to proportion; S2: adding the mixture obtained in step S1 into a high-temperature melting device, and performing melt mixing at a temperature of 350 to 400° C. to ensure that each component is fully and evenly dispersed, and the duration is 20 to 30 minutes; S3: Extruding the melt-mixed material through an extruder, with the extrusion temperature controlled between 330 and 360° C. and the extrusion speed controlled between 5 and 10 m / min; S4: Cooling the extruded sheet material, maintaining the cooling water temperature at 30-40° C., and controlling the cooling time to 10-15 minutes; S5: hot pressing the cooled sheet material, wherein the hot pressing temperature is controlled between 280 and 320° C., the hot pressing time is controlled between 5 and 10 minutes, and the pressure is controlled between 10 and 20 MPa.
[0025] S6: Post-processing the obtained high-performance polyetheretherketone board, including annealing and surface treatment, with the annealing temperature controlled between 170 and 220° C. for 1 to 2 hours to enhance its mechanical strength and thermal stability.
[0026] The present invention is further configured as follows: during the extrusion process of step S3, a high-frequency magnetic field is applied so that the carbon nanotubes and graphene nanosheets can be arranged more orderly during the melting process, and the high-frequency magnetic field has a frequency of 50 to 100 Hz, a magnetic field strength of 0.5 to 1 Tesla, and a duration of 5 to 10 minutes.
[0027] The present invention is further configured as follows: in the melt mixing process of step S2, the mixing temperature is controlled to be 375-390° C. and maintained within this temperature range for 15-20 minutes.
[0028] In step S1, the raw materials are mixed in a predetermined ratio to ensure the uniformity of the components, laying the foundation for subsequent melt mixing. In the melt mixing process of step S2, the mixing temperature is controlled between 275 and 290°C and maintained within this temperature range for 15 to 20 minutes, which effectively promotes the full compatibility and dispersion of the polyetheretherketone matrix with fillers such as carbon nanotubes and graphene nanosheets. This temperature range can optimize the dispersion effect of the filler and avoid degradation or loss of performance of the filler due to excessively high temperatures. In addition, sufficient mixing time ensures good interface bonding between the filler and the polymer matrix, thereby improving the mechanical properties, thermal stability and electrical conductivity of the material.
[0029] During the extrusion process of step S3, applying a high-frequency magnetic field can further optimize the arrangement structure of the filler. Carbon nanotubes and graphene nanosheets are orderly arranged in a molten state by the action of a high-frequency magnetic field, forming a more efficient conductive network and thermal conductivity path. The frequency of the magnetic field is 50 to 100 Hz, the intensity is 0.5 to 1 Tesla, and the duration is 5 to 10 minutes. This design can significantly improve the electrical conductivity, thermal conductivity and antistatic properties of the composite material, while avoiding excessive aggregation of fillers during the melting process, ensuring the uniformity and stability of the material.
[0030] The cooling process in step S4 helps to quickly solidify the sheet material and ensure the dimensional stability of the final product. The cooling water temperature is controlled between 30 and 40°C and the cooling time is 10 to 15 minutes, which effectively avoids the internal stress caused by too fast or too slow cooling, thereby improving the overall quality and mechanical properties of the sheet.
[0031] In step S5, the density and surface quality of the sheet are further optimized by hot pressing. The precise control of the hot pressing temperature and time helps to improve the mechanical strength and surface flatness of the composite material, ensuring the uniformity and stability of the final sheet.
[0032] Finally, the post-processing in step S6, including annealing and surface treatment, can further enhance the mechanical strength and thermal stability of the material. The annealing temperature is controlled at 150-200°C and the annealing time is 1-2 hours, which effectively eliminates the internal stress that may exist during the processing and improves the fatigue resistance and long-term stability of the polyetheretherketone board.
[0033] The beneficial effects of the present invention are as follows: the present invention significantly improves the comprehensive performance of the material by optimizing the preparation process of high-performance polyetheretherketone (PEEK) composite materials. The use of fillers such as carbon nanotubes and graphene nanosheets and coating with polyaniline or polypyrrole solves the problem of easy aggregation of these nanomaterials, ensures that they are evenly dispersed in the polyetheretherketone matrix, and enhances the mechanical properties, electrical conductivity and thermal conductivity of the material. The addition of conductive tin oxide micropowder further improves the conductive network and improves the electrical conductivity of the composite material. The use of polytetrafluoroethylene micropowder improves the wear resistance and chemical stability of the material, and is particularly suitable for applications in corrosive media such as strong acids and strong alkalis.
[0034] In addition, the magnetic powder (such as ferrite powder or nano iron powder) added during the coating process interacts with the external magnetic field to optimize the arrangement of the filler, forming an efficient conductive network and thermal conductivity path, thereby improving the antistatic performance and thermal stability of the material. The uniformity and stability of the material are ensured by precisely controlling process parameters such as melt mixing, extrusion molding and hot pressing. Post-processing steps (such as annealing) further enhance the fatigue resistance and long-term stability of the composite material. DETAILED DESCRIPTION
[0035] In order to make the technical means, creative features, objectives and effects of the present invention easier to understand, the present invention is further described below.
[0036] In the following embodiments, the polyetheretherketone used is Victrex 450G; the polytetrafluoroethylene is Dyneon TFM 1600 from 3M; the carbon nanotubes have an outer diameter of 1-2 nanometers, a length of 5-20 microns, and a surface area of 200-23 m 2 / g; the thickness of graphene nanosheets is 0.5-1 nanometers, the diameter is 5-10 micrometers, and the surface area is 500-550 m 2 / g; the average particle size of conductive tin oxide powder is 20-50 nanometers and the surface area is 90-100 m 2 / g; the silane coupling agent used is 3-methacryloxypropyltrimethoxysilane.
[0037] Example 1 This embodiment discloses a formula and a preparation method for preparing a high-performance polyetheretherketone board. The specific components and proportions are: Polyetheretherketone 85 parts Carbon Nanotubes 2 parts Graphene nanosheets 2 parts Conductive tin oxide powder 4 parts 4 parts of polytetrafluoroethylene powder Silane coupling agent 0.8 parts Preparation method S1: uniformly mix the above components according to the weight ratio to ensure that the carbon nanotubes, graphene nanosheets, conductive tin oxide powder, polytetrafluoroethylene powder and silane coupling agent are uniformly dispersed in the polyetheretherketone matrix.
[0038] S2: Add the mixture obtained in step S1 into a high-temperature melting device and perform melt mixing at a temperature of 370° C. for 25 minutes to ensure that the components are evenly dispersed.
[0039] S3: The melt-mixed materials are fed into an extruder for extrusion. The extrusion temperature is controlled at 340° C. and the extrusion speed is 8 m / min to obtain a uniform sheet material.
[0040] S4: placing the extruded sheet material into a cooling device for cooling, the cooling water temperature is controlled at 35° C., and the cooling time is 12 minutes.
[0041] S5: The cooled sheet material is hot pressed, the hot pressing temperature is controlled at 300°C, the hot pressing time is 8 minutes, and the hot pressing pressure is 15 MPa.
[0042] S6: The obtained plate is annealed at a temperature of 180° C. for 1.5 hours to enhance its mechanical properties and thermal stability.
[0043] Example 2 This embodiment discloses another formula and preparation method of high-performance polyetheretherketone board. Its specific components and proportions are: Polyetheretherketone 90 parts 1.5 parts carbon nanotubes Graphene nanosheets 1.5 parts Conductive tin oxide powder 3 parts 3 parts of polytetrafluoroethylene powder Silane coupling agent 0.6 parts Preparation method S1: Mix the above components evenly according to the proportion to ensure that the carbon nanotubes, graphene nanosheets, conductive tin oxide powder, polytetrafluoroethylene powder and silane coupling agent are evenly dispersed in the polyetheretherketone matrix.
[0044] S2: Add the mixture into a high temperature melting device and perform melt mixing at a temperature of 380°C for 22 minutes to ensure that the components are fully dispersed.
[0045] S3: The melt-mixed materials are fed into an extruder for extrusion. The extrusion temperature is set at 350° C. and the extrusion speed is 7 m / min.
[0046] S4: Cooling the extruded sheet material, controlling the cooling water temperature at 32° C., and cooling time for 13 minutes.
[0047] S5: The cooled sheet material is sent to a hot pressing machine for hot pressing. The hot pressing temperature is set to 310°C, the hot pressing time is 6 minutes, and the pressure is 18 MPa.
[0048] S6: performing annealing treatment, with the annealing temperature set at 170° C. and the annealing time set at 1.5 hours, to improve its mechanical properties and thermal stability.
[0049] Example 3 This embodiment discloses another formula and preparation method of high-performance polyetheretherketone board. Its specific components and proportions are: Polyetheretherketone 80 parts Carbon Nanotubes 3 parts Graphene nanosheets 3 parts Conductive tin oxide powder 5 parts 5 parts of polytetrafluoroethylene powder Silane coupling agent 1 part Preparation method S1: Mix the components evenly according to the proportions to ensure that the carbon nanotubes, graphene nanosheets, conductive tin oxide micropowders, polytetrafluoroethylene micropowders and silane coupling agents are evenly distributed in the polyetheretherketone.
[0050] S2: The mixture was added into a high temperature melting device and melt mixed at a temperature of 390° C. for 30 minutes to ensure complete dispersion of the components.
[0051] S3: The molten mixture was fed into an extruder for extrusion. The extrusion temperature was set at 330° C. and the extrusion speed was set at 9 m / min.
[0052] S4: placing the extruded sheet material into a cooling device for cooling, the cooling water temperature is 40° C., and the cooling time is 10 minutes.
[0053] S5: The cooled sheet material is hot-pressed, the hot-pressing temperature is set to 320°C, the hot-pressing time is 7 minutes, and the hot-pressing pressure is 20 MPa.
[0054] S6: The formed sheet is annealed at a temperature of 200°C for 2 hours to improve its mechanical strength and thermal stability.
[0055] Example 4 This embodiment discloses a high-performance polyetheretherketone board, which comprises the following components in parts by weight: Polyetheretherketone: 85 parts; Carbon nanotubes: 2 parts; Graphene nanosheets: 2 parts; Conductive tin oxide powder: 3 parts; Polytetrafluoroethylene powder: 4 parts; Silane coupling agent: 0.8 parts.
[0056] Among them, carbon nanotubes and graphene nanosheets are coated with polyaniline respectively. The specific coating process is as follows: Step 1: Prepare Materials Firstly, the carbon nanotubes and graphene nanosheets are dispersed by ultrasonic treatment to obtain a filler after surface pretreatment.
[0057] A polyaniline monomer solution was prepared with a concentration of 0.2 mol / L, and ammonium persulfate (APS) was added as an oxidant in an amount of 0.15 times the mass of the monomer.
[0058] The mass ratio of the polyaniline monomer solution to the carbon nanotubes and graphene nanosheets is 2:1.
[0059] Step 2: Coating reaction The treated carbon nanotubes and graphene nanosheets were added to the polyaniline monomer solution respectively, and stirred for reaction at 25° C. for 4 hours to complete the polyaniline coating reaction.
[0060] Step 3: Drying and crushing The product after the reaction is separated by filtration and washed with deionized water until it is neutral. The washed coating material is vacuum dried at 50°C for 24 hours, and the dried particles are crushed to 10 to 50 microns.
[0061] Next, the steps for preparing high-performance PEEK boards are as follows: S1: polyetheretherketone, coated carbon nanotubes, coated graphene nanosheets, conductive tin oxide micropowder, polytetrafluoroethylene micropowder and silane coupling agent are uniformly mixed according to proportion.
[0062] S2: Add the mixture into a high temperature melting device, set the temperature to 370°C, and melt mix for 20 minutes to ensure that the components are evenly dispersed.
[0063] S3: The molten mixture is extruded through an extruder, the extrusion temperature is set to 340° C., and the extrusion speed is controlled to 7 m / min.
[0064] S4: The extruded sheet material was cooled in cooling water at 30° C. for 15 minutes.
[0065] S5: The cooled sheet is hot pressed at a temperature of 300°C, for 7 minutes, and at a pressure of 15 MPa.
[0066] S6: The obtained plate is subjected to annealing treatment, and the annealing temperature is set to 180° C. and the time is 1.5 hours.
[0067] The resulting high-performance polyetheretherketone board has good electrical conductivity, thermal stability and mechanical properties.
[0068] Example 5 This embodiment discloses a high-performance polyetheretherketone board, which comprises the following components in parts by weight: Polyetheretherketone: 88 parts; Carbon nanotubes: 1 part; Graphene nanosheets: 1 part; Conductive tin oxide powder: 2 parts; Polytetrafluoroethylene powder: 3 parts; Silane coupling agent: 0.6 parts.
[0069] Among them, carbon nanotubes and graphene nanosheets are coated with polypyrrole respectively. The specific coating process is as follows: Step 1: Prepare Materials The carbon nanotubes and graphene nanosheets are firstly dispersed by ultrasonic to obtain the surface-treated fillers.
[0070] A polypyrrole monomer solution was prepared with a concentration of 0.2 mol / L, and ammonium persulfate (APS) was added as an oxidant in an amount of 0.2 times the mass of the monomer.
[0071] The mass ratio of the polypyrrole monomer solution to the carbon nanotubes and graphene nanosheets is 3:1.
[0072] Step 2: Coating reaction The treated carbon nanotubes and graphene nanosheets were added to the polypyrrole monomer solution respectively, and the mixture was stirred and reacted at 4° C. for 7 hours to complete the polypyrrole coating reaction.
[0073] Step 3: Drying and crushing The product after the reaction was separated by filtration and washed with deionized water until neutral. The washed coating material was vacuum dried at 55° C. for 20 hours, and the dried particles were crushed to 10 to 50 microns.
[0074] The steps for preparing high-performance polyetheretherketone boards are as follows: S1: polyetheretherketone, coated carbon nanotubes, coated graphene nanosheets, conductive tin oxide micropowder, polytetrafluoroethylene micropowder and silane coupling agent are uniformly mixed according to proportion.
[0075] S2: Add the mixture into a high temperature melting device, set the temperature to 380°C, and melt mix for 25 minutes to ensure that the components are evenly dispersed.
[0076] S3: The molten mixture was extruded through an extruder at a temperature of 340° C. and a speed of 6 m / min.
[0077] S4: The extruded sheet material was cooled in cooling water at 35° C. for 12 minutes.
[0078] S5: The cooled sheet is hot pressed at a temperature of 290°C, a time of 8 minutes, and a pressure of 18 MPa.
[0079] S6: The obtained plate is annealed at a temperature of 170° C. for 1 hour.
[0080] The resulting high-performance PEEK board has excellent electrical conductivity and thermal stability, making it suitable for high-end electronic devices.
[0081] Example 6 This embodiment discloses a high-performance polyetheretherketone board, which comprises the following components in parts by weight: Polyetheretherketone: 90 parts; Carbon nanotubes: 3 parts; Graphene nanosheets: 3 parts; Conductive tin oxide powder: 5 parts; Polytetrafluoroethylene powder: 5 parts; Silane coupling agent: 1 part.
[0082] Among them, carbon nanotubes and graphene nanosheets are coated with polyaniline respectively. The specific coating process is as follows: Step 1: Prepare Materials The carbon nanotubes and graphene nanosheets are treated with acid to obtain surface-treated fillers.
[0083] A polyaniline monomer solution was prepared with a concentration of 0.2 mol / L, and ammonium persulfate (APS) was added as an oxidant in an amount of 0.1 times the mass of the monomer.
[0084] The mass ratio of the polyaniline monomer solution to the carbon nanotubes and graphene nanosheets is 10:1.
[0085] Step 2: Coating reaction The treated carbon nanotubes and graphene nanosheets were added to the polyaniline monomer solution respectively, and stirred for reaction at 30° C. for 3 hours to complete the polyaniline coating reaction.
[0086] Step 3: Drying and crushing The product after the reaction was separated by filtration and washed with deionized water until neutral. The washed coating material was vacuum dried at 60° C. for 12 hours, and the dried particles were crushed to 20 to 50 microns.
[0087] The steps for preparing high-performance polyetheretherketone boards are as follows: S1: polyetheretherketone, coated carbon nanotubes, coated graphene nanosheets, conductive tin oxide micropowder, polytetrafluoroethylene micropowder and silane coupling agent are uniformly mixed according to proportion.
[0088] S2: Add the mixture into a high temperature melting device, set the temperature to 360°C, and melt mix for 30 minutes to ensure that the components are evenly dispersed.
[0089] S3: The molten mixture was extruded through an extruder at a temperature of 350° C. and a speed of 8 m / min.
[0090] S4: The extruded sheet material was cooled in cooling water at 40° C. for 10 minutes.
[0091] S5: The cooled sheet is hot pressed at a temperature of 310°C, for 6 minutes, and at a pressure of 12 MPa.
[0092] S6: The obtained plate is annealed at a temperature of 190° C. for 1.5 hours.
[0093] Example 7 This embodiment discloses a method for preparing a high-performance polyetheretherketone board, using the following formula and process: formula: Polyetheretherketone: 85 parts Carbon nanotubes: 2 parts Graphene nanosheets: 2 parts Conductive tin oxide powder: 4 parts Polytetrafluoroethylene powder: 4 parts Silane coupling agent: 1 part Coating process: Step 1: Prepare materials: The carbon nanotubes and graphene nanosheets were acid-treated respectively, immersed in a 1M hydrochloric acid solution for 1 hour, and then cleaned by ultrasonic wave to obtain fillers with surface pre-treated surface.
[0094] Prepare a 0.2 mol / L polyaniline monomer solution, add ammonium persulfate (APS) oxidant, and add the amount of ammonium persulfate to 0.15 times the weight of the monomer. Add ferrite powder to the solution, and the amount of ferrite powder added is 12% of the total weight of the filler.
[0095] The mass ratio of the polyaniline monomer solution to the carbon nanotubes and graphene nanosheets is 5:1.
[0096] Step 2: Coating reaction: The acid-treated carbon nanotubes and graphene nanosheets were respectively added into a polyaniline monomer solution containing ferrite powder and stirred at room temperature for 3 hours to complete the polymerization coating.
[0097] The reaction temperature was controlled at 28°C and the reaction time was 3 hours.
[0098] Step 3 Drying and crushing: The product after the coating reaction was separated by filtration and washed with deionized water until neutral. The washed material was vacuum dried at a drying temperature of 55° C. for 18 hours.
[0099] The dried coated particles were crushed to obtain coated particles with a particle size of 30 microns.
[0100] Preparation method: S1: Mix the raw materials of the above formula evenly according to the proportion. S2: The mixture was added to a high temperature melting device, the temperature was set to 385°C, and the mixing duration was 25 minutes.
[0101] S3: The melt-mixed material is extruded through an extruder, the extrusion temperature is controlled at 340°C, and the extrusion speed is 7m / min. During the extrusion process, a high-frequency magnetic field is applied, the frequency is 60Hz, the magnetic field strength is 0.8 Tesla, and the duration is 8 minutes.
[0102] S4: The extruded sheet material is cooled, the cooling water temperature is 35° C., and the cooling time is 12 minutes.
[0103] S5: hot pressing the cooled sheet material, with the hot pressing temperature being 300° C., the hot pressing time being 7 minutes, and the pressure being 15 MPa.
[0104] S6: performing annealing treatment on the obtained plate, the annealing temperature is 175° C., and the time is 1.5 hours.
[0105] Example 8 This embodiment discloses a method for preparing a high-performance polyetheretherketone board, using the following formula and process: formula: Polyetheretherketone: 88 parts Carbon nanotubes: 1.5 parts Graphene nanosheets: 1.5 parts Conductive tin oxide powder: 3 parts Polytetrafluoroethylene powder: 3 parts Silane coupling agent: 0.8 parts Coating process: Step 1: Prepare materials: The carbon nanotubes and graphene nanosheets are treated with acid and dispersed by ultrasonic waves to obtain fillers with surface pretreatment.
[0106] Prepare a polypyrrole monomer solution with a concentration of 0.2 mol / L, add ammonium persulfate (APS) oxidant in an amount of 0.15 times the weight of the monomer, and add nano iron powder in an amount of 13% of the total weight of the filler.
[0107] The mass ratio of the polypyrrole monomer solution to the carbon nanotubes and graphene nanosheets is 7:1.
[0108] Step 2: Coating reaction: The carbon nanotubes and graphene nanosheets were added into the polypyrrole monomer solution containing nano iron powder and stirred at 0°C for 7 hours to complete the polymerization coating.
[0109] The reaction temperature was controlled at 4°C and the reaction time was 7 hours.
[0110] Step 3 Drying and crushing: The product after the coating reaction was separated by filtration and washed with deionized water until neutral. The washed material was vacuum dried at a drying temperature of 55° C. for 20 hours.
[0111] The dried coated particles were crushed to obtain coated particles with a particle size of 40 microns.
[0112] Preparation method: S1: Mix the raw materials of the above formula evenly according to the proportion. S2: The mixture was added to a high temperature melting device, the temperature was set to 385°C, and the mixing duration was 25 minutes.
[0113] S3: The melt-mixed material is extruded through an extruder, the extrusion temperature is controlled at 345°C, and the extrusion speed is 7m / min. During the extrusion process, a high-frequency magnetic field is applied, the frequency is 70Hz, the magnetic field strength is 1 Tesla, and the duration is 7 minutes.
[0114] S4: The extruded sheet material is cooled, the cooling water temperature is 35° C., and the cooling time is 12 minutes.
[0115] S5: hot pressing the cooled sheet material, with the hot pressing temperature being 300° C., the hot pressing time being 7 minutes, and the pressure being 15 MPa.
[0116] S6: performing annealing treatment on the obtained plate, the annealing temperature is 175° C., and the time is 1.5 hours.
[0117] Example 9 This embodiment discloses a method for preparing a high-performance polyetheretherketone board, using the following formula and process: formula: Polyetheretherketone: 90 parts Carbon nanotubes: 3 parts Graphene nanosheets: 3 parts Conductive tin oxide powder: 5 parts Polytetrafluoroethylene powder: 5 parts Silane coupling agent: 0.5 parts Coating process: Step 1: Prepare materials: The carbon nanotubes and graphene nanosheets are treated with acid and dispersed by ultrasonic wave to obtain the fillers with surface pretreatment.
[0118] Prepare a polyaniline monomer solution with a concentration of 0.2 mol / L, add ammonium persulfate (APS) oxidant, the amount of which is 0.2 times the weight of the monomer. Select cobalt iron oxide powder as the magnetic powder, and the amount of which is 10% of the total weight of the filler.
[0119] The mass ratio of the polyaniline monomer solution to the carbon nanotubes and graphene nanosheets is 8:1.
[0120] Step 2: Coating reaction: The carbon nanotubes and graphene nanosheets were added into the polyaniline monomer solution containing cobalt iron oxide powder and stirred at room temperature for 3 hours to complete the polymerization coating.
[0121] The reaction temperature was controlled at 28°C and the reaction time was 3 hours.
[0122] Step 3 Drying and crushing: The product after the coating reaction was separated by filtration and washed with deionized water until neutral. The washed material was vacuum dried at a drying temperature of 60° C. for 24 hours.
[0123] The dried coated particles were crushed to obtain coated particles with a particle size of 25 microns.
[0124] Preparation method: S1: Mix the raw materials of the above formula evenly according to the proportion. S2: The mixture was added to a high temperature melting device, the temperature was set to 385°C, and the mixing duration was 25 minutes.
[0125] S3: The melt-mixed material is extruded through an extruder, the extrusion temperature is controlled at 340°C, and the extrusion speed is 7m / min. During the extrusion process, a high-frequency magnetic field is applied, the frequency is 80Hz, the magnetic field strength is 1.5 Tesla, and the duration is 9 minutes.
[0126] S4: The extruded sheet material is cooled, the cooling water temperature is 35° C., and the cooling time is 12 minutes.
[0127] S5: hot pressing the cooled sheet material, with the hot pressing temperature being 300° C., the hot pressing time being 7 minutes, and the pressure being 15 MPa.
[0128] S6: performing annealing treatment on the obtained plate, the annealing temperature is 175° C., and the time is 1.5 hours.
[0129] Comparative Example 1 This comparative example discloses the formula of polyetheretherketone board and its preparation method. Its specific components and proportions are: Polyetheretherketone 85 parts Carbon Nanotubes 2 parts Conductive tin oxide powder 4 parts 4 parts of polytetrafluoroethylene powder Silane coupling agent 0.8 parts Preparation method S1: The above components are mixed uniformly according to the weight ratio to ensure that the carbon nanotubes, conductive tin oxide powder, polytetrafluoroethylene powder and silane coupling agent are uniformly dispersed in the polyetheretherketone matrix.
[0130] S2: Add the mixture obtained in step S1 into a high-temperature melting device and perform melt mixing at a temperature of 370° C. for 25 minutes to ensure that the components are evenly dispersed.
[0131] S3: The melt-mixed materials are fed into an extruder for extrusion. The extrusion temperature is controlled at 330° C. and the extrusion speed is 8 m / min to obtain a uniform sheet material.
[0132] S4: placing the extruded sheet material into a cooling device for cooling, the cooling water temperature is controlled at 35° C., and the cooling time is 12 minutes.
[0133] S5: The cooled sheet material is hot pressed, the hot pressing temperature is controlled at 300°C, the hot pressing time is 8 minutes, and the hot pressing pressure is 15 MPa.
[0134] S6: The obtained plate is subjected to annealing treatment, the annealing temperature is set to 180° C., and the annealing time is set to 1.5 hours.
[0135] Comparative Example 2 This comparative example discloses the formula of polyetheretherketone board and its preparation method. Its specific components and proportions are: Polyetheretherketone 85 parts Carbon Nanotubes 2 parts Graphene nanosheets 2 parts Conductive tin oxide powder 4 parts Silane coupling agent 0.8 parts Preparation method S1: The above components are mixed uniformly according to the weight ratio to ensure that the carbon nanotubes, graphene nanosheets, conductive tin oxide powder and silane coupling agent are uniformly dispersed in the polyetheretherketone matrix.
[0136] S2: Add the mixture obtained in step S1 into a high-temperature melting device and perform melt mixing at a temperature of 370° C. for 25 minutes to ensure that the components are evenly dispersed.
[0137] S3: The melt-mixed materials are fed into an extruder for extrusion. The extrusion temperature is controlled at 350° C. and the extrusion speed is 8 m / min to obtain a uniform sheet material.
[0138] S4: placing the extruded sheet material into a cooling device for cooling, the cooling water temperature is controlled at 35° C., and the cooling time is 12 minutes.
[0139] S5: The cooled sheet material is hot pressed, the hot pressing temperature is controlled at 300°C, the hot pressing time is 8 minutes, and the hot pressing pressure is 15 MPa.
[0140] S6: The obtained plate is subjected to annealing treatment, the annealing temperature is set to 180° C., and the annealing time is set to 1.5 hours.
[0141] Comparative Example 3 This comparative example discloses the formula of polyetheretherketone board and its preparation method. Its specific components and proportions are: Polyetheretherketone 85 parts Carbon Nanotubes 2 parts Silane coupling agent 0.8 parts Preparation method S1: The above components are mixed uniformly according to the weight ratio to ensure that the carbon nanotubes and the silane coupling agent are uniformly dispersed in the polyetheretherketone matrix.
[0142] S2: Add the mixture obtained in step S1 into a high-temperature melting device and perform melt mixing at a temperature of 370° C. for 25 minutes to ensure that the components are evenly dispersed.
[0143] S3: The melt-mixed materials are fed into an extruder for extrusion. The extrusion temperature is controlled at 340° C. and the extrusion speed is 8 m / min to obtain a uniform sheet material.
[0144] S4: placing the extruded sheet material into a cooling device for cooling, the cooling water temperature is controlled at 35° C., and the cooling time is 12 minutes.
[0145] S5: The cooled sheet material is hot pressed, the hot pressing temperature is controlled at 300°C, the hot pressing time is 8 minutes, and the hot pressing pressure is 15 MPa.
[0146] S6: The obtained plate is subjected to annealing treatment, the annealing temperature is set to 180° C., and the annealing time is set to 1.5 hours.
[0147] Comparative Example 4 is a pure polyetheretherketone board.
[0148] Detection Methods The following tests were performed on the samples of Examples 1 to 9 and Comparative Examples 1 to 4.
[0149] 1. Mechanical properties test The tensile test is carried out according to ASTM D638 standard, and the test rate is generally 5 mm / min.
[0150] Three-point bending test was performed using ASTM D790 standard.
[0151] The Izod impact test was performed using the ASTM D256 standard.
[0152] The test results are shown in Table 1.
[0153] 2. Conductivity test The resistivity measurement was carried out using the four-point probe method (four-point probe method) in accordance with the ASTM D257 standard.
[0154] The test results are shown in Table 2.
[0155] The above test is the magnitude of the resistivity obtained by the test. The test shows that the magnitude of the resistivity of Examples 1-3 reaches 10 6 Ω·cm, indicating poor conductivity. The resistivity of Examples 4-6 is on the order of 10 5 Ω·cm, indicating that after carbon nanotubes and graphene nanosheets are coated with polyaniline or polypyrrole, the dispersion and interfacial bonding of fillers in the PEEK matrix are significantly improved, and the conductive network morphology is optimized, thereby reducing the resistivity. In Examples 7-9, by adding magnetic powder and applying an external magnetic field during the preparation process, the fillers can be arranged more orderly in the composite material, forming a more effective conductive path, and finally achieving a lower resistivity. Therefore, the resistivity obtained by the test is of the order of 10 4 Ω·cm.
[0156] 3. Thermal performance test The measurement is performed using the Laser Flash Method.
[0157] The test results are shown in Table 3.
[0158] The above tests show that the polyetheretherketone board prepared by the present invention has good mechanical properties, good antistatic properties and excellent thermal conductivity.
[0159] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of the present invention is defined by the attached claims and their equivalents.
Claims
1. A high-performance polyetheretherketone board, characterized in that: The composition comprises the following components in parts by weight: 80-90 parts of polyetheretherketone; 1 to 3 parts of carbon nanotubes; 1 to 3 parts of graphene nanosheets; 2-5 parts of conductive tin oxide powder; 3-5 parts of polytetrafluoroethylene powder; Silane coupling agent 0.5 to 1 part.
2. A high-performance polyetheretherketone board according to claim 1, characterized in that: The carbon nanotubes and graphene nanosheets are respectively coated with polyaniline or polypyrrole.
3. A high-performance polyetheretherketone board according to claim 2, characterized in that: Magnetic powder is mixed into the coating process, and the magnetic powder is ferrite powder, cobalt iron oxide powder or nano iron powder; the average particle size of the magnetic powder is 100 nanometers to 500 nanometers.
4. A high-performance polyetheretherketone board according to claim 3, characterized in that: The polyetheretherketone plate is subjected to an external magnetic field during the melt mixing process.
5. The high-performance polyetheretherketone board according to claim 3, characterized in that: The intensity of the external magnetic field is 0.5 to 2 Tesla.
6. The high-performance polyetheretherketone board according to claim 3, characterized in that: The coating steps are specifically as follows: Step 1: Prepare Materials: 1) Acid treatment or ultrasonic dispersion of carbon nanotubes and graphene nanosheets to obtain surface pretreated fillers; 2) preparing a monomer solution of polyaniline or polypyrrole, the concentration of which is 0.2 mol / L, and adding an oxidant to start the polymerization reaction, wherein the oxidant is ammonium persulfate, and the amount added is 0.1 to 0.2 times the mass of the monomer; at the same time, selecting magnetic powder and dispersing it in the monomer solution of polyaniline or polypyrrole, and the amount added of the magnetic powder is 10 to 15% of the mass of the filler; Wherein, the mass ratio of the polyaniline or polypyrrole monomer solution to the carbon nanotubes and graphene nanosheets is 2:1 to 10:1; Step 2: Coating reaction: adding the treated carbon nanotubes and graphene nanosheets to a monomer solution of polyaniline or polypyrrole containing magnetic powder, respectively, and stirring at room temperature for 2 to 4 hours to complete the polymerization coating; For polyaniline coating reaction, the temperature should be controlled at 25-30°C, and the reaction time should be 2-4 hours; for polypyrrole coating reaction, the temperature should be controlled at 0-5°C, and the reaction time should be 6-8 hours; Step 3: Drying and crushing: The product after the coating reaction is separated by filtration and washed with deionized water until it is neutral; the washed coating material is vacuum dried, the temperature is controlled at 50-60°C, and the drying time is 12 to 24 hours; the dried coated particles are crushed to obtain the desired particle size, and the particle size range is 10-50 microns.
7. The high-performance polyetheretherketone board according to claim 3, characterized in that: In the coating process, the amount of magnetic powder coated on the carbon nanotubes is 1-3% of the total weight of the carbon nanotubes, and the amount of magnetic powder coated on the graphene nanosheets is 3-5% of the total weight of the graphene nanosheets.
8. A method for preparing a high-performance polyetheretherketone board according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Mix the various raw materials of the high-performance polyetheretherketone board evenly according to proportion; S2: adding the mixture obtained in step S1 into a high-temperature melting device, and performing melt mixing at a temperature of 350 to 400° C. to ensure that each component is fully and evenly dispersed, and the duration is 20 to 30 minutes; S3: Extruding the melt-mixed material through an extruder, with the extrusion temperature controlled between 330 and 360° C. and the extrusion speed controlled between 5 and 10 m / min; S4: Cooling the extruded sheet material, maintaining the cooling water temperature at 30-40° C., and controlling the cooling time to 10-15 minutes; S5: hot pressing the cooled sheet material, wherein the hot pressing temperature is controlled between 280 and 320° C., the hot pressing time is controlled between 5 and 10 minutes, and the pressure is controlled between 10 and 20 MPa; S6: performing post-treatment on the obtained high-performance polyetheretherketone board, including annealing and surface treatment, wherein the annealing temperature is controlled between 170 and 220° C. and the time is 1 to 2 hours.
9. The method for preparing a high-performance polyetheretherketone board according to claim 8, characterized in that: During the extrusion process of step S3, a high-frequency magnetic field is applied, wherein the frequency of the high-frequency magnetic field is 50-100 Hz, the magnetic field strength is 0.5-1 Tesla, and the duration is 5-10 minutes.
10. The method for preparing a high-performance polyetheretherketone board according to claim 8, characterized in that: During the melt mixing process of step S2, the mixing temperature is controlled to be 375-390°C and maintained within this temperature range for 15-20 minutes.
Citation Information
Cited By
Conductive PEEK film and preparation method thereof
CN120648202A
High-strength high-temperature-resistant anti-static polyether-ether-ketone composite material for electronic equipment and preparation method thereof
CN120888174A
High-performance polyether-ether-ketone modified sealing material and preparation method thereof
CN121271208A